AMPHIBIAN AND REPTILE DIVERSITY IN THE NAPO-PUTUMAYO-AMAZONAS INTERFLUVIUM, NORTHERN PERUVIAN AMAZON - TAPIA-DEL-ÁGUILA, Carlo Jaminton (2020)
Knowledge of the biodiversity of amphibians and reptiles is essential in developing conservation for these taxa. We collected data from visual encounters and bibliographic review to determine the diversity of amphibians and reptiles in different habitats in the Putumayo–Napo–Amazonas interfluvium. This interfluvium presents 140 species of amphibians and 108 reptiles. The hill forest had the highest species richness, with 58 species of amphibians and 40 species of reptiles. The richest families were Hylidae and Colubridae. The Hilids presented a greater number of species in flooded ecosystems, while the Craugastoridae and Bufonidae families had greater richness in non-flooded ones. The Colubridae family was present in both ecosystems, although with a greater presence in flooded habitats. A community similarity analysis showed two groups: one formed by the amphibians of the high terrace, middle terrace and hill forest forests, and a second group from the low terrace, palm swamp, and peatland pole forest. In the reptiles, two groups were also formed: one by the reptiles of the palm swamp, hill forest and high terrace, and the second group made up of the reptiles of the low terrace forest, middle terrace and peatland pole forest. This diversity is threatened by deforestation, agriculture, caiman hunting and turtle egg collection, if intensified, could cause drastic population declines in these species.